Investigation to the Reducibility of Iron Oxide Pellets at LISCO and its Effects on Their Compressive Strength - Aljarany, Ali; Alhrouse, Mohammed; Abosenena, Nasr-Aldeen (Conference On Engineering Science and Technology, 2021)
In this paper, the reducibility of the iron oxide pellets imported by LISCO (CVRD, LKAP and SAMARCO) and its effects on their compressive strength were investigated. Direct reduction processes of the oxide pellets were conducted in the production furnace at LISCO, in order to simulate the real conditions (Midrex process) for the reduction of the selected iron oxide pellets individually – for each type. The compressive strength of the reduced (at 876ºC ±10) pellets were also, tested using the compression test machine (1000 KNf) available at LISCO. Compressive strength results showed, the LKAP pellets have the highest compressive strength, if compared with CVRD and SAMARCO pellets respectively. The obtained results also, revealed controversial relationship between the degree of reduction (metallization) and the compressive strength for all types of pellets. The reduced LKAP pellets (For all sizes) showed the lowest metallization degree, and the highest compressive strength. Conversely, the reduced SAMARCO (For all sizes) pellets recorder the highest metallization degree, but the lowest compressive strength.  Generally, the small sizes of all types of reduced pellets have higher reducibility and compressive strength, if compared with medium and big size pellets
Keywords: Iron ore; Pressure resistant; Direct reduced method; Midrex method